2012
DOI: 10.1042/cbi20110183
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow derived mesenchymal stem cells from aged mice have reduced wound healing, angiogenesis, proliferation and anti‐apoptosis capabilities

Abstract: Decline in the function of stem cells with age, such as other cells of the body, results in an imbalance between loss and renewal. Increasing age of the donor thus diminishes the effectiveness of MSCs (mesenchymal stem cells) transplantation in age-related diseases. The clinical use of stem cell therapies needs autologous stem cell transplantation; it is essential therefore to study the repair ability and survivability of cells before transplantation. Bone marrow derived MSCs possess multi-lineage differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 30 publications
3
77
0
1
Order By: Relevance
“…They also found that the migration of MSCs isolated from older donors (rat and human) was not significantly impaired compared with the MSCs from young donors [135] . In contrast to this last finding, Choudery described that MSCs from aged mice exhibit diminished effectiveness and increased expression of apoptotic and senescent genes [136] . In this review, we have described different techniques for improving MSC homing and the expression of homing molecules on MSCs.…”
Section: Caveats In Modifying Homing Moleculesmentioning
confidence: 76%
“…They also found that the migration of MSCs isolated from older donors (rat and human) was not significantly impaired compared with the MSCs from young donors [135] . In contrast to this last finding, Choudery described that MSCs from aged mice exhibit diminished effectiveness and increased expression of apoptotic and senescent genes [136] . In this review, we have described different techniques for improving MSC homing and the expression of homing molecules on MSCs.…”
Section: Caveats In Modifying Homing Moleculesmentioning
confidence: 76%
“…34 Age-related increases in the expression of apoptotic and senescent genes with a concomitant decrease in Sirt1 gene expression also inhibits stem cell function to some degree. 35 These findings suggest that the age of BMSC donors should be considered in regard to their therapeutic efficacy. This interference further suggests that the loss of young BMSC exosome-specific miRNAs is related to cancer, because the development of the majority of cancers is considered to be related to age.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the controversial embryonic stem cells, MSCs could be isolated from many ethically palatable tissues such as bone marrow [16,17], adipose tissue [17,18], liver [19,20], muscle [21,22], amniotic fluid [23,24], placenta [25,26], umbilical cord blood [16,27], dental pulp [28,29]. However, it is generally observed that the biological activity and therapeutic potency of MSCs correlate inversely with developmental stage of the donor [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Therefore, MSCs from ethically and socially controversial but "young" tissues such as fetal tissues [49] and human embryonic stem cells (ESCs) [50] continue to be investigated for their therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%